Fluoride Retention following the Professional Topical Application of 2% Neutral Sodium Fluoride Foam - Wenqun Song; Shinji Toda; Eri Komiyama; Karin Komiyama; Yuki Arakawa; Dawei He; Hirohisa Arakawa (Hindawi Limited, 2011)
The objective of the present research was to determine the appropriate amount of fluoride to use professional topical application and the residual amounts of fluoride in the oral cavity using a 2% neutral sodium fluoride (NaF) foam with a dedicated tray. Using dentition study models, a method for determining the appropriate amount of NaF foam was investigated. In eight adult subjects, the appropriate amount of NaF foam, the concentration of fluoride in the saliva following professional topical application, and the amount of residual fluoride in the oral cavity following professional topical application was examined. The results indicated that the appropriate amount of NaF foam was approximately 0.8 g, the amount of residual fluoride in the oral cavity was approximately 25% of the amount of foam used.